Enhancing farmers’ access to technology for increased rice productivity in Ghana - Buah, Saaka S.J.; Nutsugah, S.K.; Kanton, R.A.L.; Atokple, I.D.K.; Dogbe, W.; Karikari, A.S.; Wiredu, A.N.; Amankwah, A.; Osei, C.; Ajayi, O.; Ndiaye, K. (Academic Journals, 2011)
A two-year emergency rice (Oryza sativa L.) initiative was launched in 2009 in response to the globalrice crises in 2008. The objective of this initiative in Ghana was to increase rice productivity in order toimprove food security. Project activities included planning sessions, demonstrations, training coursesand community seed production. The project made remarkable progress in enhancing access to qualityseed and fertilizer for over 12,600 farmers while expanding knowledge of best-bet productiontechnologies. Farmers produced 28,663 Mt of paddy which was 16,841 Mt above what they normallyproduced without project intervention. Average yield increased by 92% and also 4,093 women farmersconstituting about 32.4% of the total number of participating farmers benefited directly from the project.Seed fairs, rural radios and audio-visual broadcasts on improved rice production technologies wereused to reach non-participating farmers. The combination of methods that stimulated adoption ofimproved rice production technology was effective in achieving both increased paddy yields andhousehold income. We conclude that investment in rice technology transfer and production effortsduring the two-year period was well justified.